Metode Pelaksanaan FOndasi Tiang Pancang Pada Proyek Pembangunan Gedung Perpustakaan Kabupaten Kulon Progo - , TENGKU ANNISA, Ir. Sri Winarni ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Infrastructure growth is now growing rapidly not only in big cities, but also in rural areas. No exception to the villages in Kulon Progo which is currently being very intensive doing regional development activities to improve and advance the quality of people life in Kulon Progo. One of other the ways is to building the library. The purpose of this report is to Know and to describe the stages of erection of pile fondation on the library building project in Kulon Progo Regency, Yogyakarta. In this report, the method used is the method of observation, interviews, literature and documentation methods. Based on those method, it able to concluded the advantages and disadvantages of using pile foundations in the implementation of building construction of library kulon progo.